1911 Ohio Acts 124-25, An Act to prohibit the manufacture and sale of certain kinds of weapons, §§ 1-2 (vol. 102) - (:unkn) unknown (My University, 1911)
Whoever manufacturers, sells or exposes for sale, any weapon known or designated as brass knuckles, billy, slung-shot, sand-bag, black-jack or other weapon of similar character, shall, for the first offense be fined not less than ten dollars nor more than fifty dollars, and for the second and subsequent offenses, shall be fined not less than one hundred dollars nor more than five hundred dollars and imprisoned not less than thirty days nor more than six months.
Keywords: TRANSFER